Gambaran Monitoring Gula Darah Kasus Diabetes Melitus di Puskesmas ‘X’ Kota Dumai - Elda Nazriati; Fifia Chandra; Izfhathaniah Izfhathaniah (Fakultas Kedokteran Universitas Riau, 2018)
Diabetes mellitus is a metabolic disease that has 2 main targets of treatment, keeping the glucose levels within normal range, and preventing complications. The purposed of this research is to know the description of blood glucose monitoring consisting of fasting blood glucose, HbA1C, and self monitoring blood glucose (SMBG). This was a qualitative research by using observation method and deep interview to ten informant. The results showed the checkup of fasting blood glucose levels have been going well with some obstacles, for instance, running out of glucose strips. Puskesmas ‘X’ did not perform HbA1C checkup due to unavailability of laboratory equipment. Overall DM patients did not perform SMBG because they did not have the device, but the researchers obtained one patient who had a device at home, but the patient still chose to check his blood glucose at the puskesmas because the low knowledge of the patient to perform SMBG.